Increase in Simultaneous Coexpression of Naive and Memory Lymphocyte Markers at Diagnosis of IDDM - Smerdon, Rebecca A; Peakman, Mark; Hussain, Munther J; Alviggi, Lorenzo; Watkins, Peter J; Leslie, R David G; Vergani, Diego (Diabetes (New York, N.Y.), 1993)
The monoclonal antibodies 2H4 (antl-CD45RA) and UCHL1 (antl-CD45RO) were used to subdivide the CD4 and CD8 T-cell subsets into naive and memory cells. The peripheral blood lymphocytes of 34 patients with recent-onset IDDM, 21 patients with long-standing IDDM, and healthy control subjects of similar age and sex were analyzed by a three-color immunofluorescence technique. CD4 and CD8 lymphocytes expressed the CD45 isoforms alone (CD45RA+ or CD45RO+) or in combination (CD45RA+RO+). Simultaneous coexpression of both CD45RA and CD45RO (CD45RA+RO+) on CD4 and CD8 lymphocytes in patients with recent-onset IDDM was higher than in control subjects (P < 0.001). The proportion of CD4 lymphocytes expressing CD45RA alone (CD45RA+RO−) was similar in these groups, but the percentage of CD8 lymphocytes that were CD45RA+RO− was significantly higher in the patients with recent-onset IDDM (P < 0.05). The result of these changes is a significant increase in expression of naive phenotypes (CD45RA+ and CD45RA+RO+) on CD4 and CD8 lymphocytes in recent-onset IDDM (P < 0.005 and P < 0.0001). In long-standing IDDM, total CD45RA+ expression on CD4 and CD8 lymphocytes was reduced compared with control subjects (P < 0.05) as a result of a tendency of CD45RA+RO+ and CD45RA+RO+ subsets to be lower. This increase in total naive (CD45RA+) lymphocytes and in coexpression of naive (CD45RA) and memory (CD45RO) markers on CD4 and CD8 lymphocytes subsets In patients with recent-onset IDDM suggests that abnormal regulation of T-cell activation andmaturation is important in the pathogenesis of the disease.